2024
DOI: 10.3390/cancers16020365
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Imaging Biomarkers of Response to Signaling Inhibition Therapy in Melanoma

Pradeep Kumar Gupta,
Stepan Orlovskiy,
Fernando Arias-Mendoza
et al.

Abstract: Dabrafenib therapy for metastatic melanoma focuses on blocking growth-promoting signals produced by a hyperactive BRAF protein. We report the metabolic differences of four human melanoma cell lines with diverse responses to dabrafenib therapy (30 mg/kg; oral): WM3918 < WM9838BR < WM983B < DB-1. Our goal was to determine if metabolic changes produced by the altered signaling pathway due to BRAF mutations differ in the melanoma models and whether these differences correlate with response to treatment. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Published research, including ours, shows that magnetic resonance spectroscopy (MRS) is a noninvasive avenue for monitoring metabolic changes in melanoma models following diverse anticancer treatments [10,11]. We demonstrated that MRS discerns significant changes in metabolic signatures in successfully treated melanoma models with dabrafenib, a BRAF inhibitor, showcasing early therapy-related changes in metabolomics, pH, and bioenergetics [10]. This elucidation underscores the potential of MRS in delineating early-treatment metabolic responses to targeted therapies.…”
Section: Figure 6 (Previous Page)mentioning
confidence: 68%
See 4 more Smart Citations
“…Published research, including ours, shows that magnetic resonance spectroscopy (MRS) is a noninvasive avenue for monitoring metabolic changes in melanoma models following diverse anticancer treatments [10,11]. We demonstrated that MRS discerns significant changes in metabolic signatures in successfully treated melanoma models with dabrafenib, a BRAF inhibitor, showcasing early therapy-related changes in metabolomics, pH, and bioenergetics [10]. This elucidation underscores the potential of MRS in delineating early-treatment metabolic responses to targeted therapies.…”
Section: Figure 6 (Previous Page)mentioning
confidence: 68%
“…In addition, the comparison of slopes for pHe of DB-1 between untreated (m = -0.020) and trametinib treated (m = 0.010) was statistically significant (p = 0.02). Published research, including ours, shows that magnetic resonance spectroscopy (MRS) is a noninvasive avenue for monitoring metabolic changes in melanoma models following diverse anticancer treatments [10,11]. We demonstrated that MRS discerns significant changes in metabolic signatures in successfully treated melanoma models with dabrafenib, a BRAF inhibitor, showcasing early therapy-related changes in metabolomics, pH, and bioenergetics [10].…”
Section: Figure 6 (Previous Page)mentioning
confidence: 90%
See 3 more Smart Citations